Prevalence of methicillin-resistant Staphylococcus aureus in stray cats around colleges of Universiti Putra Malaysia and selected neighbourhoods of Seri Serdang, Selangor, Malaysia - Abdul Ghani, Azlan Shah; Hassan, Latiffah; Zakaria, Zunita (2010)
The existence of Methicillin-resistant Staphylococcus aureus (MRSA) is due to the widespread utilization of antimicrobial agents. Besides humans, MRSA has not only been reported in livestock animals but also in pet animals such as the dogs and cats. This study was designed to estimate the prevalence of MRSA in stray cats around colleges of Universiti Putra Malaysia (UPM) and in selected neighbourhood of Sri Serdang. The samples for this study were taken from the nostrils of the stray cats using small sterile cotton swabs. The swabs were then inoculated onto blood agar (BA) and suspected colonies were gram stained. Gram positive cocci bacteria colonies were then inoculated onto mannitol salt agar (MSA) and yellowish colonies that grew were subjected to a series of biochemical tests such as the catalase, coagulase and Staphytect Plus latex agglutination test before they were inoculated onto the oxacillin resistance screening agar base (ORSAB). A total of seven (12.73%) MRSA from 55 samples were isolated from the stray cats. The results showed that the prevalence of MRSA in stray cats at colleges of Universiti Putra Malaysia and Seri Serdang are high (>10%). The stray cats may have contracted MRSA from contact with infected humans or via contaminated environments at the health care facilities such as the Student Medical Centre which is located in the college area of UPM and also from consuming contaminated raw meat from markets in Sri Serdang.